Glycerol kinase deficiency in adults: Description of 4 novel cases, systematic review and development of a clinical diagnostic score. (December 2020) - Lamiquiz-Moneo, Itziar; Mateo-Gallego, Rocio; Fernández-Pardo, Jacinto; López-Ariño, Chuan; Marco-Benedí, Victoria; Bea, Ana M.; Ferraro, Lia; Jarauta, Estibaliz; Cenarro, Ana; Civeira, Fernando
Abstract: Background and aims: Glycerol kinase deficiency (GKD) is a rare genetic disorder characterized by hyperglycerolemia and glyceroluria, which could be misdiagnosed as a moderate to severe hypertriglyceridemia (HTG). We aimed to describe four novel cases of GKD, to complete a systematic review of all cases of isolated GKD published so far, and to develop a suspicion clinical diagnostic score for GKD. Methods: We reported four cases with suspicion of GKD and compared their phenotype with 584 males with triglycerides (TG) > 300 mg/dL, selected as control group (HTG non-GKD). The GK gene was sequenced in all cases. Lipoprotein particle concentrations were measured in all cases with GKD. The systematic review involved a PubMed, Cochrane and Scopus databases search to identify anthropometric and biochemical characteristics of all described cases with GKD. Results: The systematic review retrieved a total of 15 articles involving 39 subjects with GKD. GKD cases reported a history of high TG levels resistant to lipid-lowering therapy. Compared to GKD subjects (n = 43), HTG non-GKD subjects (n = 584) showed significantly higher BMI, total cholesterol, non-HDL cholesterol and gamma-glutamyltransferase, significantly lower HDL cholesterol and TG, and higher prevalence of diabetes. The proposed diagnostic score was significantly higher in GKD than in HTG non-GKD subjects. Conclusions: This is the first systematic review that compiles all GKD cases reported to date including 4 novel cases, and examine the differential GKD phenotype compared to other types of HTG. The proposed score would have a broad utility in clinical practice to avoid unwarranted lipid lowering treatment in GKD patients. Graphical abstract: Image 1 Highlights: Glycerol kinase deficiency (GKD) is a rare genetic disorder often misdiagnosed as hypertriglyceridemia (HTG). We describe 4 novel GKD cases and complete the first systematic review compiling all published subjects with GKD. The distinctive clinical features between GKD and HTG patients are described. This study proposes the first pseudo-HTG diagnostic score.